Flavonoid Distribution in Asplenioid Ferns - Y., Umikalsum; J. B., Harborne (1991)
In a survey of 15 representatives of the Asplenioid ferns for the pinnae flavonoids, kaempferol was found in 80 %, quercetin 53% and proanthocyanidin 13% of the species studied. Kaempferol3 O-methyl ether was found in A. marinum only. Acacetin and genkwanin have been previously found in the fern, Notholaena bryopoda (Polypodiaceae), but for the first time in A. normale. This is the second report of the occurrence of this type off lavoneinferns. Hispidulin and pectolinangenin were detected inA. glaucophyllum in trace amounts due to the small sample and at a relatively low concentration. Scutellarein was detected inA. belangeri. To our knowledge, this is the first report of the existence of hispidulin, pectolinangenin and scutellrein in ferns.